Therapeutic effects of adropin on glucose tolerance and substrate utilization in diet-induced obese mice with insulin resistance - Su Gao; Ryan P. McMillan; Qingzhang Zhu; Gary D. Lopaschuk; Matthew W. Hulver; Andrew A. Butler (Elsevier, 2015)
Objective: The peptide hormone adropin regulates fuel selection preferences in skeletal muscle under fed and fasted conditions. Here, we investigated whether adropin treatment can ameliorate the dysregulation of fuel substrate metabolism, and improve aspects of glucose homeostasis in diet-induced obesity (DIO) with insulin resistance. Methods: DIO C57BL/6 mice maintained on a 60% kcal fat diet received five intraperitoneal (i.p.) injections of the bioactive peptide adropin34-76 (450 nmol/kg/i.p.). Following treatment, glucose tolerance and whole body insulin sensitivity were assessed and indirect calorimetry was employed to analyze whole body substrate oxidation preferences. Biochemical assays performed in skeletal muscle samples analyzed insulin signaling action and substrate oxidation. Results: Adropin treatment improved glucose tolerance, enhanced insulin action and augmented metabolic flexibility towards glucose utilization. In muscle, adropin treatment increased insulin-induced Akt phosphorylation and cell-surface expression of GLUT4 suggesting sensitization of insulin signaling pathways. Reduced incomplete fatty acid oxidation and increased CoA/acetyl-CoA ratio suggested improved mitochondrial function. The underlying mechanisms appear to involve suppressions of carnitine palmitoyltransferase-1B (CPT-1B) and CD36, two key enzymes in fatty acid utilization. Adropin treatment activated pyruvate dehydrogenase (PDH), a rate-limiting enzyme in glucose oxidation, and downregulated PDH kinase-4 (PDK-4) that inhibits PDH. Along with these changes, adropin treatment downregulated peroxisome proliferator-activated receptor-gamma coactivator-1α that regulates expression of Cpt1b, Cd36 and Pdk4. Conclusions: Adropin treatment of DIO mice enhances glucose tolerance, ameliorates insulin resistance and promotes preferential use of carbohydrate over fat in fuel selection. Skeletal muscle is a key organ in mediating adropin's whole-body effects, sensitizing insulin signaling pathways and altering fuel selection preference to favor glucose while suppressing fat oxidation.